Pelatihan dan Pendampingan Pencatatan Keuangan di UMKM Rindu.Id di Kabupaten Jember - Amalina Maryam Zakiyyah (Indonesian Journal Publisher, 2021)
SMEs have an important role in the economy, but to be able to develop, many of them face problems, there are capital access andmarketing. The difficulty of accessing capital is because SMEs do not yet have financial reports. This program aims to socializethe benefits of small business financial management, conduct training on daily recording transactions, and prepare financialreports. For the socialization of small business financial management, the accounting cycle and financial management benefitboth personal and institutional are presented. Then the implementation practice of delivering socialization materials. Therecording of daily transactions and preparation of financial reports follows the rules of SAK ETAP with many conveniences forSMEs compared to PSAK, which has more complex reporting requirements. From assisting the preparation of financialstatements, we can produce income statements and reports on changes in capital. We encountered problems when preparing abalance sheet because of Rindu.Id does not have current asset reports and inventory reports in the warehouse.